Benign myoepithelioma of the hard palate: a clinical and histological diagnostic challenge. Case report and literature review - Maffi-Berthier Louis; Le pelletier François; Ejeil Anne-laure (EDP Sciences, 2018)
Introduction: Myoepithelioma (ME) is a rare salivary gland tumor. Constructed aroung a clinical case, this article aims to gather up up-to-date epidemiological, clinical and histological data about myoeptihelioma with emphasis on the diagnostic approach and differential diagnoses, paraclinical exams and the main histological features reported for its characterization. Observation: A 41-year-old female, presenting a 1-year slowly enlarging palatine nodule was referred to the Oral Pathology Consultation. Clinical data and paraclinic examination were non-specific. A thorough histological examination, comparing clinical data with cyto-architectural and immunostaining profile of the tumor allowed a positive diagnosis of ME. Discussion: The clinical aspect of ME is close from other more frequent tumors within the same areas. Accordingly, its discovery is often incidental and its diagnosis histological. ME display variable architecture and composition, requiring full tumor examination for proper diagnosis. When benign, ME act as mixed tumor regarding local extension, prognosis and recurrence. Malignant ME behaves as a low-grade malignant tumor with metastatic potential. Conclusion: Despite its rarity, ME should be hypothesized in front of a palatine nodule. Clinician and pathologist should be particularly cautious regarding nature, malignancy and follow-up of this tumor, since few data are up-to-now available.